A review of population-based prevalence studies of physical activity in adults in the Asia-Pacific region - Macniven Rona; Bauman Adrian; Abouzeid Marian (BMC, 2012)
Abstract Background Physical activity (PA) surveillance is an important component of non-communicable disease risk factor monitoring, and occurs through national and international surveillance systems. This review identifies population PA estimates for adults in the Asia-Pacific region, and examines variation in trends and prevalence rates obtained using different PA measures. Methods Data were obtained from a MEDLINE search; World Health Organization's Global Health Infobase; Government websites and reference lists of relevant papers. Inclusion criteria included: national studies or those reporting large scale population-level data; data published from 2000 to 2010 and trend data prior; sample sizes over n = 1000, or fewer subjects in small nations. Results In total, 56 population surveys from 29 Asia-Pacific countries were identified. Data on 'sufficient physical activity' amongst adults were available from 45 studies (80%), with estimates ranging from 7% to 93% (median 62%, inter-quartile range 40%-85%). For 14 countries, estimates of 'sufficient activity' were documented in multiple surveys using different methods, with the largest variation from 18% to 92% in Nepal. Median or mean MET-minutes/day, reported in 20 studies, ranged from 6 to 1356. Serial trend data were available for 11 countries (22%), for periods spanning 2-10 years. Of these, five countries demonstrated increases in physical activity over time, four demonstrated decreases and three showed no changes. Conclusions Many countries in the Asia-Pacific region collect population-level PA data. This review highlights differences in estimates within and between countries. Some differences may be real, others due to variation in the PA questions asked and survey methods used. Use of standardized protocols and measures, and combined reporting of data are essential goals of improved international PA surveillance.